2012
DOI: 10.1186/1471-244x-12-94
|View full text |Cite
|
Sign up to set email alerts
|

Screening for personality disorder in incarcerated adolescent boys: preliminary validation of an adolescent version of the standardised assessment of personality – abbreviated scale (SAPAS-AV)

Abstract: BackgroundPersonality disorder (PD) is associated with significant functional impairment and an elevated risk of violent and suicidal behaviour. The prevalence of PD in populations of young offenders is likely to be high. However, because the assessment of PD is time-consuming, it is not routinely assessed in this population. A brief screen for the identification of young people who might warrant further detailed assessment of PD could be particularly valuable for clinicians and researchers working in juvenile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 64 publications
5
31
2
Order By: Relevance
“…The study also adds to the literature in general in personality disorder in adolescent psychopathology; for instance, rates of personality disorder between 28% and 64% have been found in anorexia and 25% in eating disorder not otherwise specified, 23,24 and rates of between 36% and 88% for psychopathy and callous and unemotional traits within adolescent forensic populations. 25 Such rates are thus broadly comparable with our findings in adolescent self-harm.…”
Section: Discussionsupporting
confidence: 88%
“…The study also adds to the literature in general in personality disorder in adolescent psychopathology; for instance, rates of personality disorder between 28% and 64% have been found in anorexia and 25% in eating disorder not otherwise specified, 23,24 and rates of between 36% and 88% for psychopathy and callous and unemotional traits within adolescent forensic populations. 25 Such rates are thus broadly comparable with our findings in adolescent self-harm.…”
Section: Discussionsupporting
confidence: 88%
“…Figure displays the ROC curve for the SAPAS as a screen for a SCID‐II criterion diagnosis of any PD in the sample. The ROC curve for a well‐performing test deviates significantly from the 45° reference line (AUC = 0.5), where no discrimination exists, and approaches the ‘ideal test point’ (AUC = 1), where sensitivity and specificity both equal 100% and the false positive rate is 0% (Kongerslev et al, ; Kraemer, ). In our sample, the ROC curve for the sample was statistically highly significantly different ( p < 0.001) from the 45° reference line.…”
Section: Resultsmentioning
confidence: 99%
“…As shown by Day and Schriger [14], small numbers deviate more from the percentage agreement regression line, while higher numbers deviate less. This is why some researchers use at least 5 cases per cell for their analyses – leaving some criteria with a low prevalence despite the fact that both raters have a high level of agreement [4,6,15-17]. In such cases, some investigators have reported good percentage agreement accompanied by an undesirable Cohen’s Kappa [14]; however, this situation does not occur when using Gwet’s AC1.…”
Section: Discussionmentioning
confidence: 99%